E-Governance and AI Integration: A Roadmap for Smart Governance Practices - Srivastava, Mukul; Sharma, Neelu (Samsad Journal संसद जर्नल, 2025)
E-Government's incorporation of Artificial Intelligence (AI) has transformed governance models by increasing public accountability, efficiency, and transparency. The political communication process in India has changed as a result of AI-driven initiatives, which have made governance more open, data-driven, and citizen-focused. Natural Language Processing (NLP), machine learning, and predictive analytics are examples of AI applications that have revolutionized public service delivery, automated administrative tasks, and enhanced parliamentary decision-making. With an emphasis on India's digital governance transformation, this research paper examines how AI integration has improved transparency in e-government. AI powered chatbots, automated legal research tools, and digital grievance redressal mechanisms have streamlined citizen-government interactions, reducing bureaucratic inefficiencies and fostering public trust. Initiatives like the Supreme Court’s AI powered SUPACE system, the National Informatics Centre’s AI-driven data analytics, and Umang’s AI-based citizen services exemplify how AI has enabled greater transparency in governance. The impact of AI on governance is critically examined in this paper, with particular attention paid to how it can reduce corruption, enhance public access to information, and guarantee real-time monitoring of governmental operations. In order to show how AI integration in Indian e-government has set an example for digital democracy, this study analyzes secondary data from government reports, policy documents, and international assessments. It also discusses challenges such as data privacy concerns, algorithmic biases, and the digital divide, which may affect AI’s equitable adoption. The results highlight how India's AI-enabled e-government reforms have improved administrative effectiveness while also bolstering democratic engagement by increasing the accessibility and transparency of political communication. The study comes to the conclusion that India's model provides a path for the adoption of AI in parliamentary procedures worldwide, guaranteeing inclusive, accountable, and technologically advanced governance.